Carotenoids and Human Health - Tanumihardjo, Sherry A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2013)
Carotenoids and Human Health provides an introduction to food sources and metabolism. Written by experts in their fields and including the most up-to-date information, this volume serves as an in-depth guide to studies that have been performed in humans and observations that have been made in population level assessments. Special emphasis is given to associations with disease, as well as the importance of carotenoids internationally, specifically as a source of vitamin A for the world. Comprehensive and easy to use, Carotenoids and Human Health is a very useful resource for nutritionists, registered dieticians, medical students, and graduate students.
Food Sources of Carotenoids -- Carrots of Various Colors -- Carotenoid Metabolism and Enzymology -- Reactive Oxygen and Nitrogen Species in Biological Systems: Reactions and Regulation by Carotenoids -- Kinetic Studies with Carotenoids -- Carotenoid Bioavailability: Influence of Dietary Lipid and Fiber -- Host Factors that Affect Carotenoid Metabolism -- Host Factors: Gender and Body Composition -- Carotenoid Metabolism and Health in Pregnancy and Lactation -- Carotenoids in Early Life -- Provitamin A Carotenoids and Cancer Prevention -- Lycopene and Cancer -- Lutein and Zeaxanthin and Eye Disease -- Carotenoids and Bone Health -- Provitamin A Carotenoids as a Dietary Source of Vitamin A -- Provitamin A Carotenoids and Immune Function -- Biofortification of Maize with Provitamin-A Carotenoids -- Horticultural Crops as a Source of Carotenoids -- Orange Sweetpotato as a Staple or Complementary Food -- International Efforts to Eradicate Vitamin A Deficiency.
Keywords: Medicine; Personal health and hygiene; Medicine & Public Health; Clinical Nutrition; Health Promotion and Disease Prevention